Spanish for translators in training: draft of a proposal - Cebey, María del Mar; Escalante, Alba; Ramos-Nogueira, Luis Carlos (Onomázein, 2022)
More than a decade ago, on the occasion of the First Congress of Sworn Translators of Uruguay (CTPU 2011), we presented some reflections that portrayed the work recently undertaken in the Spanish translation course at the Universidade de Brasília, Brazil. It was the beginning of our course and, at that time, our teaching experience provoked more questions than answers. One of the main topics of discussion concerned the approach to language classes in a training course for translators. As Beeby (2004) mentions, the fundamentals of language teaching in the context of translator training envolve studying each case in its particularity. The purpose of this proposal is to present the ideas we have been outlining in order to answer our questions about the specificity of ELE teaching in the specific context of translator training in the Spanish-Portuguese language pair. These ideas are initially presented, followed by some of the aspects that particularize our proposal, the context of its implementation and, by way of illustration, a set of didactic activities.